Hospital exposure as a risk factor for the transmission of measles: A case-control study in Turkey. - Serap Çetin Çoban; Selmur Topal; Fehminaz Temel; Muharrem Öncül; Bao-ping Zhu; Levent Akın (Turkish Society of Public Health Specialists, 2016)
Objective: During a nationwide measles epidemic in 2013, we conducted an investigation in Sanliurfa province to assess risk factors for measles infections. Methods: In a case-control design, we compared the history of hospital exposures for 189 randomly selected laboratory-confirmed patients (aged <15 years) residing in the central district and control-individuals matched for neighbourhood and age. We estimated the effectiveness of the vaccine (VE). Results:For infants from 0-11 months, 53.8% of the case and 23.8% of the controls had visited a hospital during one the month prior to the onset of the case's rash (ORadj=3.7, 95% CI=1.6-8.6). For children from 1-6 years, 48.2% of the cases  and 14.3% of the controls visited a hospital during one month prior to the onset case's rash (ORadj=5.5,95% CI=2.5-12.8) and  59.7% of cases had not completed one dose of measles vaccine  by 12 months, compared with  14.7% of controls (ORadj=7.4,95% CI=2.1-26.9; VE=86%,95% CI=52-96%). For children from 7- 14 years, 53.8% of the cases had not completed one dose of measles vaccination by age 12 months, compared with 15.4%  of controls (ORadj=6.7,95% CI=1.7-26.6; VE=85%, 95% CI=41-96%). Conclusion: We conclude that the hospitals facilitated measles transmission during this epidemic. We recommend triage febrile patients and patients with a rash in healthcare settings, and strengthening measles vaccination programme.. Keywords: Measles; Measles Vaccine; Nosocomial Infections; Risk Factors; Case Control Study